Global tensions : challenges and opportunities in the world economy - Benería, Lourdes; Bisnath, Savitri, 1965- (Routledge, 2004)
Composed of original essays by renowned scholars, this volume explores controversial topics such as free trade, women's rights, labor standards, the World Trade Organization and global tensions.